Positive Psychology in Prison: Prisoner's Happy Review from Self Forgiveness and Hope - Dwi Puspasari; Nelia Afriyeni; Yuni Dwi Rahma; Nola Chentya Yuni; Nurul Azizah (Budapest International Research and Critics University, 2022)
Happiness is a positive psychological concept that has several influencing factors, including forgiveness or willingness to let go of self-hatred for mistakes and hope or a positive mental state about the ability to achieve goals. This study aimed to examine the influence of self-forgiveness and hope for prisoners' happiness. The measuring instrument used were the Oxford Happiness Questionnaire by Michael Argyle and Peter Hills (∑item = 29) for happiness, the Heartland Forgiveness Scale (∑item = 18) for forgiveness (in this study just used one subscale), and The Adult Hope Scale (AHS) (∑item = 12) for hope. The results of this study found that there was a simultaneous positive effect of forgiveness and hope on happiness with a significance of .000. The practical contribution given is 25%, which means that forgiveness and hope have an effect of 25% on the level of happiness in inmates at the Lapas Klas IIB Solok.